The discourse of child counselling - Hutchby, Ian (Impact, studies in language and society ;, 2007)
This book is an empirical study of naturally occurring interaction between child counselling professionals and young children experiencing parental separation or divorce. Based on tape recordings of the work of a London child counselling practice, it offers the reader a unique and sustained look inside the child counselling consultation room at the talk that occurs there. The book uses conversation analysis against a backdrop of sociological work in childhood and family studies to situate the discourse of child counselling at an interface between the increasing incitement to communicate in mod.